Trajnostni prostorski razvoj in novejši procesi v prostorskem razvoju Ljubljane - Rebernik, Dejan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2007)
The main goal of the paper is to identify, analyse and evaluate the basic processes in spatial development in Ljubljana. In the first part of the paper the main theoretical and planning concepts of sustainable urban development as well as goals and aims of Slovene spatial policy regarding urban development are presented. Characteristics and processes of recent urban development of Ljubljana are presented in five themes: inner urban development, derelict urban areas, areas of dispersed urbanisation, functional transformation and mixed urban land use and residential areas.
Keywords: Ljubljana; urbana geografija; mesta; urbanizacija; prostorski razvoj; sustainable development; trajnostni razvoj; sonaravni razvoj